Life Experiences in the New Normal: Interpersonal Communication, Work Values and Job Commitment of Young Professionals - Balatbat-Paglinawan, Karen Cristina; Mel Paglinawan, William (International Journal of Humanities and Education Development (IJHED), 2022)
The pandemic has hit every single employee detrimentally, leaving each one feeling worried about how to make ends meet especially in this new normal. Using qualitative measures to probe the living experiences of the young professionals in the highly affected economic sectors of General Santos City - Philippines, eight-core themes were extracted using Moustakas’ (1994) modified van Kaam phenomenological analysis. Results revealed that the economic uncertainty, as well as the psychological and personal consequences brought by the pandemic, have kept young professionals staying in their existing jobs; thus, allowing them to seek multiple employment. It was found out that young professionals developed a certain perspective towards employment, making job security a central aspect in staying committed to their jobs. More so, the participants manifested a dynamic communication style which became one of the essential aspects of expressing concern in the organization and they also regarded family values as a driving force in striving to live. Findings also revealed that it was not the nature of adversity, such as the threat brought by the pandemic, that was most important, but how individuals dealt with it. In this paper, when young professionals faced adversity or frustration in this new normal, protective factors of resilience, work values, commitment and communication helped them survive, recover, and even thrive in the face and wake of misfortunes.